2021
DOI: 10.1111/1752-1688.12912
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Impacts of Nutrient Loading, Warming, and Boundary Exchanges on Hypoxia and Metabolism in a Shallow Estuarine Ecosystem

Abstract: We sought to investigate the impacts of nutrient loading, warming, and open‐water boundary exchanges on a shallow estuary through idealized numerical model experiments. We performed these simulations using a stand‐alone implementation of the Regional Ocean Modeling System‐Row‐Column AESOP biogeochemical model in the Chester River estuary, a tributary estuary within the Chesapeake Bay estuarine complex. We found that metabolic rates were elevated in the shallow tributary creeks of the estuary relative to open w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Many previous studies have examined long‐term changes in hypoxic volume in estuaries (Carstensen et al, 2014; Hagy et al, 2004; Murphy et al, 2011; Scavia et al, 2006), including simulated responses to future climate change (Cai et al, 2021; Irby et al, 2018; Laurent et al, 2018; Meier et al, 2011; Ni et al, 2020). Fewer studies, however, have examined detailed metabolic responses that exert influences on changes in hypoxic volume (Li et al, 2016; Testa et al, 2021). Murphy et al (2011) reported significant increases in early summer hypoxia and a slight decrease in late summer hypoxia in Chesapeake Bay over a 60‐year period, where climate‐related variables (e.g., elevated stratification) were one explanation for the early‐summer increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have examined long‐term changes in hypoxic volume in estuaries (Carstensen et al, 2014; Hagy et al, 2004; Murphy et al, 2011; Scavia et al, 2006), including simulated responses to future climate change (Cai et al, 2021; Irby et al, 2018; Laurent et al, 2018; Meier et al, 2011; Ni et al, 2020). Fewer studies, however, have examined detailed metabolic responses that exert influences on changes in hypoxic volume (Li et al, 2016; Testa et al, 2021). Murphy et al (2011) reported significant increases in early summer hypoxia and a slight decrease in late summer hypoxia in Chesapeake Bay over a 60‐year period, where climate‐related variables (e.g., elevated stratification) were one explanation for the early‐summer increase.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change is expected to alter precipitation and temperature patterns that are expected to influence hypoxia via changes in nutrient inputs, metabolic rates, stratification, and oxygen solubility (Irby et al, 2018; Laurent et al, 2018; Meier et al, 2011; Ni et al, 2019). Chesapeake Bay is expected to have larger hypoxic volumes in the future associated with climate change, given that contemporary warming has already compensated for expected improvements from nutrient loading (Ni et al, 2020) and that warmer temperatures are expected to reduce oxygen concentrations through many pathways (Irby et al, 2018; Ni et al, 2019; Testa et al, 2021). Climate change impacts on precipitation will also influence hypoxia, as interannual variations in river flow are a key driver of hypoxia through stratification enhancement and elevated nutrient inputs (Hagy et al, 2004; Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Testa et al (2022) shift the investigation of climate change impact on DO from the mainstem of Chesapeake Bay to a shallow tributary, the Chester River, located on the eastern shore of the Bay. Shallow estuarine systems have several unique characteristics compared to larger, deeper systems.…”
Section: Overview Of the Featured Collectionmentioning
confidence: 99%
“…The outstanding influence of this feature indicates caution is necessary in any attempt to generalize results of climate change among different estuaries. Testa et al (2022) shift the investigation of climate change impact on DO from the mainstem of Chesapeake Bay to a shallow tributary, the Chester River, located on the eastern shore of the Bay. Shallow estuarine systems have several unique characteristics compared to larger, deeper systems.…”
Section: Temperature Effects On Chesapeake Baymentioning
confidence: 99%
“…Future estimates of coastal hypoxia have increased substantially over the past decade, likely influenced by increased access to biogeochemical modeling tools and regional climate projections needed for finer scale modeling and analyses (Fennel et al, 2019). The majority of coastal hypoxia climate impact studies have focused on a select few coastal locations including the Baltic Sea (Meier et al, 2011a,b;Meier et al, 2012;Neumann et al, 2012;Ryabchenko et al, 2016;Saraiva et al, 2019a,b;Wåhlström et al, 2020;Meier et al, 2021;Meier et al, 2022), Chesapeake Bay (Wang et al, 2017;Irby et al, 2018;Ni et al, 2019;Testa et al, 2021;Tian et al, 2021;Cai et al, 2021), and the Gulf of Mexico (Justić et al, 1996;Justić et al, 2007;Lehrter et al, 2017;Laurent et al, 2018). Other projected changes to dissolved oxygen (O2) levels have been documented in nearshore environments including the North Sea (Meire et al, 2013;Wakelin et al, 2020), Arabian Sea (Lachkar et al, 2019), California Current System (Dussin et al, 2019;Siedlecki et al, 2021;Pozo Buil et al, 2021), and coastal waters surrounding China (Hong et al, 2020;Yau et al, 2020;Zhang et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%